On the influence of contact tribology on brake squeal - Hetzler, H.; Willner, Kai (Tribology International, 2012)
This contribution aims at introducing tribological contact properties into the stability analysis of macroscopic structural systems with focus on brake-squeal applications. First, the surfaces of several brake pads at different states of wear are analyzed experimentally. Based on these data a statistical contact model as well as a numerical simulation are presented. Using these models two constitutive contact laws are derived, which link contact pressure and stiffness. Second, a simple brake model incorporating these contact models is developed. Results of stability analyses are presented and the influence of the contact models on the steady state stability is discussed. © 2011 Elsevier Ltd.
Keywords: Brake squeal; Contact stiffness; Friction induced vibrations; Rough surface